Autophagy May Allow a Cell to Forbear Pyroptosis When Confronted With Cytosol-Invasive Bacteria - Harvest, Carissa K.; Miao, Edward A. (Frontiers in Immunology, 2022)
Inflammatory caspases detect cytosol-invasive Gram-negative bacteria by monitoring for the presence of LPS in the cytosol. This should provide defense against the cytosol-invasive Burkholderia and Shigella species by lysing the infected cell via pyroptosis. However, recent evidence has shown caspase-11 and gasdermin D activation can result in two different outcomes: pyroptosis and autophagy. Burkholderia cepacia complex has the ability invade the cytosol but is unable to inhibit caspase-11 and gasdermin D. Yet instead of activating pyroptosis during infection with these bacteria, the autophagy pathway is stimulated through caspases and gasdermin D. In contrast, Burkholderia thailandensis can invade the cytosol where caspasae-11 and gasdermin D is activated but the result is pyroptosis of the infected cell. In this review we propose a hypothetical model to explain why autophagy would be the solution to kill one type of Burkholderia species, but another Burkholderia species is killed by pyroptosis. For pathogens with high virulence, pyroptosis is the only solution to kill bacteria. This explains why some pathogens, such as Shigella have evolved methods to inhibit caspase-11 and gasdermin D as well as autophagy. We also discuss similar regulatory steps that affect caspase-1 that may permit the cell to forbear undergoing pyroptosis after caspase-1 activates in response to bacteria with partially effective virulence factors.